Endovascular management for acute aortic thrombosis presenting with critical lower limb ischemia - Wubulikasimu Wulamu; Hai-Lei Li; Yiu Che Chan; Stephen Wing-Keung Cheng (Vascular Investigation and Therapy)
We report a 72-year-old male presented with 8 days’ history of sudden onset of right lower limb coldness, pain, and numbness. Emergency computed tomography angiography showed occlusion of the infrarenal abdominal aorta. Emergency angiography showed complete occlusion of the infrarenal aorta extending into both common iliac arteries. The patient underwent endovascular catheter-directed thrombolysis and subsequent transfemoral thrombectomy due to distal embolism after thrombolysis and made a full recovery with well-perfused feet afterward. Acute aortic thrombosis is an unusual cause of bilateral lower limb ischemia. Prompt diagnosis and intervention were essential for limb salvage. In selected patients, endovascular treatment may provide a more minimally invasive treatment option.